أثر التسويق الإلكتروني على ولاء الزبائن للشركات السياحية في الأردن: الدور المعدل لشبكات التواصل الاجتماعي - عودة، محمد حسام أحمد; مخامرة، هبة زكي خليل Makhamrah, Hebah Zaki Khalil; عنيزان، بلال محمد; الشناق، فادي محمد (الجامعة الإسلامية بغزة - شئون البحث العلمي والدراسات العليا, 2020)
هدفت الدراسة الحالية إلى التعرف على أثر التسويق الإلكتروني في ولاء الزبائن في شركات السياحة في الأردن فضلا عن بيان الدور المعدل الذي يمكن أن تؤديه مواقع التواصل الاجتماعي في تلك العلاقة. وقد توصل الباحث إلى مجموعة من النتائج كان من أهمها أن التسويق الإلكتروني لا يؤثر معنويا من خلال مزيجه (المنتج، التسعير، الترويج، التوزيع) في كل من ولاء الزبائن بأبعاده (الولاء الاتجاهي، الولاء السلوكي) بصورة مجتمعة أو منفردة. كما أظهرت النتائج أن مواقع التواصل الاجتماعي تعدل العلاقة ما بين التسويق الإلكتروني وكل من (الولاء الاتجاهي، الولاء السلوكي)، وفي ضوء هذه النتائج قدم البحث مجموعة من التوصيات منها، أن على الشركات المبحوثة إعادة النظر باستراتيجية التسويق الإلكتروني فيها وإعادة صياغة هذه الاستراتيجية بعناصرها المختلفة، كما أوصى البحث بضرورة الاستفادة من الفرص التي توفرها مواقع التواصل الاجتماعي، كما أوصت الباحثة بضرورة إعادة صياغة استراتيجية التسويق الإلكتروني في الشركات المبحوثة وذلك لتعزيز حالة الولاء لدى عملائها ولإعادة تشكيل المكانة الذهنية لتلك الشركات في أذهانهم.
The aim of current study is to identify the impact of e-marketing on customer loyalty in Jordanian tourism companies, as well as the relationship of the amended statement role that could be played by social networking sites. The most important of the numerous results found in the research would be that e-marketing is not morally effected by its combination (product, pricing, promotion, distribution) of customer loyalty, by excluding it collectively or individually (directional loyalty, behavioral loyalty). The results also demonstrated the rate at which social networking sites modulated the relationship between e-marketing and customer loyalty (directional loyalty, behavioral loyalty). In light of these results, the study made a series of recommendations and suggestions. First, the researched companies should reconsider theire-marketing strategies and redraft them with their various elements. Second, the study recommends taking advantage of the opportunities made by different social networking sites (context, content, composition of aggregates, recommending customers, communication, interdependence, and trade). Also, the research recommended the consolidation ofe-marketing strategies and the reformulation of these strategies in the companies researched, in order to enhance their customer loyalty by: raising the level of the on-exports of the surveyed companies, working to take advantage of it by promoting loyalty among different customers, and through the reformation of the stature of mind of the companies in the minds of their customers, for the purpose of exploiting the different social networking sites.
Keywords: التسويق الإلكتروني -- سلوك المستهلك -- الشركات السياحية -- الإدارة السياحية -- الأردن